Molecular evidence for trans-stadial and transovarial transmission of Babesia occultans in Hyalomma marginatum and Rhipicephalus turanicus in Turkey - Aktas, Munir; Vatansever, Zati; Ozubek, Sezayi (Elsevier Science Bv, 2014)
A total of 1064 adult ticks identified as Hyalomma marginatum (n = 965), Rhipicephalus turanicus (n = 86), Haemaphysalis inermis (n = 9) and Rhipicephalus bursa (n= 4) along with 20 egg masses derived from H. marginatum (n = 18) and R. bursa were screened for Babesia occultans. The ticks were combined into 328 pools and infection rates were calculated as the maximum likelihood estimation (MLE) with 95% confidence intervals (CI). Of these pools, 23 (7%) were positive for B. occultans, and the overall MLE was calculated as 2.27% (CI 1.48-3.35). Infection prevalence in tick species was 7.09% for H. marginatum (22/310, MLE 2.41, CI 1.55-3.59) and 7.14% for R. turanicus (1/14, MLE 1.11, CI 0.07-5.18). None of H. inermis and R. bursa was infected with the parasite. Host-seeking H. marginatum females displayed an infection prevalence of 1.68%(2/119, MLE 0.63, CI 0.11-2.06), while no parasite DNA was detected in the males. The prevalence of infection in feeding H. marginatum varied, ranging from 27.27% (9/33, MLE 4.61, CI 2.26-8.52) in males to 25.92% (7/27, MLE 8.22, CI 3.72-15.75) in females. Of the egg masses examined, 4(22.22%) of H. marginatum and 1 (50%) of R. turanicus were infected with B. occultans. To the best of our knowledge, this is the first time that B. occultans has been detected in R. turanicus. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Hyalomma marginatum; Rhipicephalus turanicus; Babesia occultans; PCR